Grammatical information in an Aymara dictionary - Huanca Quispe, Jaime (1999)
The purpose of a dictionary -whether it is called Vocabulary, Lexicon or Dictionary- is to provide lexical information about a given language or languages, which means that in a work of this type we will find, in alphabetical order, the list of nouns, adjectives, verbs, adverbs, etc. The dictionary provides this kind of information because the person who consults it is basically looking for the meaning of the words and, if possible, something about how to use them.